Analisis Penerapan Akuntansi Manajemen Lingkungan Dalam Pengungkapan Biaya Lingkungan Berdasarkan Perspektif Islam - Ayu Apriani; Nurwani Nurwani; Yenni Samri Juliati (Jurnal Ilmiah Ekonomi Islam, 2023)
In this modern economic era there are various rumors related to the surrounding area such as global warming, eco-efficiency. There are many illustrations of the interrelated issues of environmental degradation due to waste and exploitation. Environmental issues are becoming increasingly interesting to research along with the advancement of technology and global economy. This research seeks to reveal the application of environmental accounting in the disclosure of environmental costs based on an Islamic perspective at the sei baruhur plantation office of PT Perkebunan Nusantara III. This type of research uses qualitative methods, which are included in field research. The results showed that the analyzed company applies the ISO 14001 standard, from the environmental cost disclosure segment the company still does not carry out accounting practices in the form of comprehensive disclosure, and does not yet have a special accounting segment that deals with environmental issues. However, there has been a positive effort to provide simple details even though it is only about waste management, which can be considered a form of voluntary disclosure. Based on the Islamic Perspective, the implementation of Environmental Management Accounting and disclosure of environmental costs has been carried out in accordance with Islamic provisions.